Promoting thriving at work and waning turnover intention: A relational perspective - Ghulam Abid; Irum Zahra; Alia Ahmed (Future Business Journal, 2016)
Intense competition in the business world has compelled top management to seek ways, through which they can achieve competitive edge. Both practitioners and academics understand that a sustainable competitive advantage over competitors is inextricably linked with human resource. Human resource is about maintaining human capital for organizations. It is associated with individual thriving at workplace; and, retaining top performers or skilled labor force. This study examines the antecedents of thriving at work and turnover intention among software developers. Data were gathered from 128 software developers working in a private software house. The study finds support for the positive theoretical relationship between perceived organizational support and relational resource i.e. heedful relating. Moreover, the empirical evidence suggests that perceived organizational support and heedful relating are useful predictors of thriving at work and help in reducing turnover intention.
Keywords: 650